2021
DOI: 10.1101/2021.06.23.21259176
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Averting an outbreak of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) in a university residence hall through wastewater surveillance

Abstract: A wastewater surveillance program targeting a university residence hall was implemented during the spring semester 2021 as a proactive measure to avoid an outbreak of COVID-19 on campus. Over a period of 7 weeks from early February through late March 2021, wastewater originating from the residence hall was collected as grab samples 3 times per week. During this time, there was no detection of SARS-CoV-2 by RT-qPCR in the residence hall wastewater stream. Aiming to obtain a sample more representative of the res… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 60 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…Other studies also reported similar range of SARS-CoV-2 concentration both in the university resident hall’s wastewater and WWTP’s influent using the CP Select method. For example, A range of 2.4⍰10 4 - 4⍰10 4 copies/L of SARS-CoV-2 gene was reported in the residence hall wastewater using the CP Select method during the surveillance at the University of Windsor (Corchis-Scott et al, 2021) while it was in the range from 10 3 - 2⍰10 5 copies/L for WWTP’s influent samples (Forés et al, 2021; Lynch et al, 2021). Although these data are mostly similar to the concentration found in this study, however, there is highly likely to have a different concentration of SARS-CoV-2 in wastewater as it mostly depends on the density of the COVID-19 infected people staying in those area during the sampling time, demographic location, pattern of the sewerage system, and wastewater characteristics (Barua et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies also reported similar range of SARS-CoV-2 concentration both in the university resident hall’s wastewater and WWTP’s influent using the CP Select method. For example, A range of 2.4⍰10 4 - 4⍰10 4 copies/L of SARS-CoV-2 gene was reported in the residence hall wastewater using the CP Select method during the surveillance at the University of Windsor (Corchis-Scott et al, 2021) while it was in the range from 10 3 - 2⍰10 5 copies/L for WWTP’s influent samples (Forés et al, 2021; Lynch et al, 2021). Although these data are mostly similar to the concentration found in this study, however, there is highly likely to have a different concentration of SARS-CoV-2 in wastewater as it mostly depends on the density of the COVID-19 infected people staying in those area during the sampling time, demographic location, pattern of the sewerage system, and wastewater characteristics (Barua et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Virus concentration is crucial in the wastewater especially when viral titers are very low, as is seen in building-based surveillance (Corchis-Scott et al, 2021; Gibas et al, 2021). Polyethylene glycol (PEG)-based precipitation was initially widely used to concentrate the virus with successful signal detection ((La Rosa et al, 2020; Wu et al, 2020a; Kumar et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wastewater access points were identified downstream of the dormitories/barracks at each base within the United States. To sample the wastewater, a tampon (OB Ultra Absorbency, Edgewell Personal Care, Shelton, CT) was connected by a resilient line attached to a carabiner and placed in the wastewater stream as previously described for 24-96 hours (Corchis-Scott et al, 2021). After retrieval, samples were placed in sealed bags and spiked with a storage control if samples were to be stored for more than one day, Bovine Syncytial Respiratory Virus (BRSV) vaccine (Inforce 3, Zoetis Inc., Kalamazoo, MI).…”
Section: Methodsmentioning
confidence: 99%
“…The passive sampling methodology, the use of a commercial-grade tampon, was chosen for its simple design and inexpensive cost, and because it required minimal expertise to implement (Bivins et al,2021; Corchis-Scott et al, 2021). Sampling consists of placement of the tampon in the wastewater stream for a period of time, in our case, 24-96 hours.…”
Section: Conclusion and Limitationsmentioning
confidence: 99%